1. The problem statement, all variables and given/known data Synchronous demodulate x(t). 2. Relevant equations xc(t) = cos(2pi*fc*t), fc is the carrier frequency xm(t) = cos(2pi*fm*t), fm is the modulation frequency x(t) = xc(t)*(1+m*xm(t)), m is the modulation index m = .8 fc = 2000 hz fm = 200 hz 3. The attempt at a solution I really don't even know where to start. I know synchronous demodulation means I multiply x(t) by a function, but how do I come up with that function? I realise that I could divide x(t) by (1+m*xm(t)), but that doesn't seem to be what the problem is asking.